Seguridad humana, en el contexto de la lucha contra el terrorismo (2008)
In the early 1990, the United Nations Program for Development, introduced the concept of human security which was intended to present an idea to have security as a starting point for the individual and human rights from a broad perspective. This vision has undergone conceptual changes resulting from the fight against terrorism and new forms of violent confrontation. The text analyzes changes and discussion of the concept of human security and the strategies implemented in the fight against new threats, including terrorism.